The Performance Of Rubber Clones During The Pre-Tapping Period In Pathanapuram Taluk Of Quilon District - Sreekantan Nair N (Department of Plantation Crops and Spices, College of Horticulture, 1993)
An attempt was made to assess the performance of rubber plantations during the pretapping period of Pathanapuram taluk of Quilon district. Primary data were collected through personal visits and interviews with the help of a pretested questionnaire. Secondary data were gathered from the records available at the regional office and field offices of the Rubber Board. For the study, 100 units were selected randomly from among those who planted rubber in 1986 and availed the subsidy from the Rubber Board. The region has the topography well suited for the rubber cultivation with good soil and climatic features. There has been a tendency for raising higher number of plants per unit area than what is recommended. Only in two units, planting density was between 401 to 450 per ha. Regarding planting distance in 53 units the growers have adopted the recommended planting distance. Even in these cases, close planting is noticed in the boundaries. In majority of the cases, pitting and refilling were found to be as per recommended package of practices. All the growers used advanced clones for planting. The most popular planting material used was RRII 105 which covered hundred per cent of the area under study. Majority of growers have used polybagged plants, advanced planting material. The trees were sturdy with average vigour and the clones had a fair degree of tolerance to abnormal leaf fall disease caused by phytophthora species under normal prophylactic measures. But it was susceptible to pink disease as seen from the details already furnished. The plants were free from serious wind damage as branch development was kept balanced. Discriminatory fertilizer application was not adopted by majority of the farmers in surveyed areas. However, intercropping was popular. The crops grown were plantain, banana, tapioca, yam, dioscoria. Only 46 growers out of 100 had planted leguminous cover crop. Higher density increased the immaturity period. This has been brought out by the study. All the trees had not attained tappable girth even after seven years of growth. More extension effort in reducing the stand per hectare during immaturity period is highly essential. In general, maintenance of plantations during the pretapping period was satisfactory. But there is further scope for improvement so as to reduce immaturity period. There is also a tendency among growers to open trees for tapping before attaining the recommended standard girth. It is interesting to note that eventhough majority of growers are literate, they seem to be less receptive especially about the optimum planting density and tapping stage.